Methods of Generation and Detailed Characterization of Millimeter-Scale Plasmas Using a Gasbag Target - Li, Zhi-Chao (志超李); Zheng, Jian (坚郑); Jiang, Xiao-Hua (小华蒋); Wang, Zhe-Bin (哲斌王); Yang, Dong (冬杨); Zhang, Huan (欢章); Li, San-Wei (三伟李); Wang, Feng (峰王); Peng, Xiao-Shi (晓世彭); Yin, Qiang (强尹); Zhu, Fang-Hua (芳华朱); Guo, Liang (亮郭); et al. (Chinese physics letters, 2011)
Gasbag targets are useful for the research of laser-plasma interactions in inertial confinement fusion, especially in the laser overlapping regime. We report that on the Shenggnang-II laser facility, millimeter-scale plasmas are successfully generated by four 0.35 mu m laser beams using a gasbag target. Multiple diagnostics are applied to characterize the millimeter-scale plasmas in detail. The images from the x-ray pinhole cameras confirm that millimeter-scale plasmas are indeed created. An optical Thomson scattering system diagnoses the electron temperature of the CH filling plasmas by probing the thermal ion-acoustic fluctuations, which indicates that the electron temperature has a 600 eV flat roof in 0.7-1.3 ns. Another key parameter, i.e. the electron density of the millimeter-scale plasmas, is inferred by the spectrum of the back stimulated Raman scattering of an additional 0.53 mu m laser beam. The inferred electron density keeps stable at 0.1n sub(c)in early time consistent with the controlled filling pressure and splits into a higher density in late time, which is attributed to the blast wave entering into the SRS interaction region